FISILIBILITY STUDY PENAMBAHAN VILLA PADA PT. BAGUS AGRO PELAGA DI KABUPATEN BADUNG (DENGAN PENDEKATAN ASPEK KEUANGAN DAN PEMASARAN) - Wijaya, Bagus Arya; Sumerta, I Komang; Perdanawati, Luh Putu Virra Indah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.03.TAHUN. 2021, 2021)
The purpose of this study is to determine whether or not the investment in additional villas by PT. Bagus Agro Pelaga in terms of marketing and financial aspects, with analysis techniques using Market Share, Payback Period, Net Present Value, Profitability Index, Internal Rate of Return, and Average Rate of Return. The marketing strategy used is to maintain a high level of customer satisfaction, relationship marketing, and preparation of complementary products with the concept of one stop shopping. The pricing strategy used is based on perceived value pricing, namely the price is determined by the buyer's impression (perception) of the product being offered, at a competitive price so that all customers can be served well, with promotional strategies carried out in the form of advertising, personal selling, and the public. relation. The results of the measurement of the financial aspects show that the Payback Period = 5 years; Positive Net Present Value = Rp. 9,201,370,532, -; Profitability Index = 2.06; Internal Rate of Return = 26.12% and Average Rate of Return = 36%. Judging from the various aspects of the feasibility study that was studied, with more depth on the aspects of marketing and finance, it shows positive results. So that the investment plan to add villas to PT. Bagus Agro Pelaga is worth doing.